Pemisahan dan identifikasi komponen-komponen utama minyak atsiri dari daun cengkeh segar dan kering (syzygium aromaticum) - martha tuganyita; Sanusi Gugule; I Dewa Ketut Anom (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2019)
This study aims to separate and identify the main components of essential oils from fresh clove and dried clove leaves through a steam distillation process. The resulting are dried with Na2SO4 and obtained 0.6203 mL of fresh clove oil and 2.2014 mL of dried clove oil. Clove oil was identified using IR and GC-MS. IR analysis shows that fresh oil has a wavelength of 3510.45-3448.72 cm-1 and the presence of an OH group, 2924.09-2846.93 cm-1, there is an aliphatic C-H group, 3070.68 cm-1 the presence of a benzene C-H group and 1604.77 cm-1 indicate the presence of benzene groups. Dry clove oil has a wavelength of 3518.16-3456.44 cm-1, the presence of OH groups, 2931,8-2846.3 cm-1, the presence of aliphatic C-H groups, 3070,68 cm-1 presence of C-H benzene groups and 1604,77 cm-1 indicate the presence of benzene groups. The results of the GC-MS chromatogram analysis of fresh clove oil and dried clove oil showed 7 peaks which showed 7 compounds. Of the 7 peaks produced, the highest peak has similarities with the chromatogram of eugenol and caryophyllene.